2021
DOI: 10.3390/nano11041035
|View full text |Cite
|
Sign up to set email alerts
|

Drying-Time Study in Graphene Oxide

Abstract: Graphene oxide (GO) exhibits different properties from those found in free-standing graphene, which mainly depend on the type of defects induced by the preparation method and post-processing. Although defects in graphene oxide are widely studied, we report the effect of drying time in GO and how this modifies the presence or absence of edge-, basal-, and sp3-type defects. The effect of drying time is evaluated by Raman spectroscopy, UV-visible spectroscopy, and transmission electron microscopy (TEM). The tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…1 a). The wrinkled structure is associated with surface defects due to the deviation from sp 2 to sp 3 character as a consequence of a high density of oxygen functional groups 32 , 37 . After the reduction process, rGO is characterized by well-defined and impurity-free nanosheets with slightly wrinkled regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 a). The wrinkled structure is associated with surface defects due to the deviation from sp 2 to sp 3 character as a consequence of a high density of oxygen functional groups 32 , 37 . After the reduction process, rGO is characterized by well-defined and impurity-free nanosheets with slightly wrinkled regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman analyses were performed to further corroborate the transformation of GO into rGO ( Figure 3 a,b, respectively). As is typical for oxidized graphenes, two characteristic peaks are observed in GO and rGO: (i) the D peak at 1349 cm −1 is attributed to the breathing mode of aromatic carbon rings, which is Raman active by structural defects [ 32 ], and (ii) the G peak at 1588 cm −1 is due to the C-C stretching mode in the sp 2 hybridized carbon structure [ 46 ]. A detailed analysis using Lorentz functions shows the existence of three prominent bands: the D band (yellow line), the G band (green line), and the D’ band (blue line).…”
Section: Resultsmentioning
confidence: 99%
“…After the oxidation process, 50 mg of graphite oxide flakes were dispersed in 500 mL of distilled water by sonication for 0.5 h [ 25 ]. The resulting solution was centrifuged to separate GO from non-exfoliated graphite oxide particles [ 32 ]. Under agitation, 1.0 g citric acid (CA) was added to the centrifuged suspension, setting the reduction temperature at 368 K. The precipitated rGO was collected, washed with distilled water by centrifugation, and dried at 353 K for 2 h to obtain rGO powder [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another entry on reduced GO has been reported by Toulbe et al [7], who have found that this nanomaterial is capable of inhibiting the photodegradation of α-lipoic acid (an antioxidant) in the presence of Au and Ag nanoparticles, with important implications in pharmaceutical compounds. As a complementary insight into both of the aforementioned studies, Tene and co-workers present an elegant study on how the drying conditions of GO critically affect its structure and nature of defects [8]. The same authors report also on the environmental advantages of reduced GO by efficiently removing water pollutants [9].…”
mentioning
confidence: 99%